EVALUATION OF EFFECTIVENESS BASED ON THE ANALYSIS OF THE STRUCTURE AND ALGORITHMS OF STRING DATA (Web of Technology: Multidimensional Research Journal, 2024)
In data structures, a string is a sequence of characters used to represent text. Strings are commonly used in computer programs to store and manipulate textual data. They can be manipulated using various operations such as concatenation, substring extraction, and comparison.